STUDY OF PRIMARY SCHOOL TEACHER COMPETENCE IN TANAH BUMBU REGENCY - Dwi Atmono; Muhammad Rahmattullah (JPDI (Jurnal Pendidikan Dasar Indonesia), 2017)
Teacher competence is central factor that influencing teacher performance to create human resources with certain quality. Teacher competence influenced by many factors, such as educational background and teaching experience for his specific subject. This study aims to: 1) map the competence of primary school teachers in Tanah Bumbu Regency, and 2) analyze the effect of educational background and teaching experience to teacher competence. This study used quantitative approach. Population of this research is all primary school teachers in Tanah Bumbu regency which already followed Online Test of Teacher Competence (UKG Online) as many as 1,106 teachers. Samples were taken by using purposive random sampling as much as 20% of the total population that numbered 160 people. Variables of this study are: 1) Teacher Competence, 2) Educational Background and 3) Teaching Experience. This study used quantitative analysis includes percentage technique and multiple linear regressions. The results showed: 1) Primary school teacher competence in Tanah Bumbu Regency is above the national average score of 53.05, but still below the Minimum Competence Standards (SKM) of 55. The average score of pedagogic competence is 48.15 and professional competence is 55.91. 2) There is a significant simultaneous effect of educational background and teaching experience to teacher performance. Partially, only teacher experience variable that that significantly influence the teacher competence.